Analyzing the Impact of Implementation of the Belt and Road Initiative on the Malaysian Economy in 2018-2022 - Ramadhan, Megah Rahmat; Widhiyoga, Ganjar; Wijayati, Hasna (Insignia: Journal of International Relations, 2024)
This research is motivated by the Belt and Road Initiative program, which aims to create a new trade route connecting China to various countries using the Silk Route. The project was created through cooperation between China and many countries, including Malaysia. Malaysia rejected the BRI in 2018 but continued with a new agreement. This study aims to determine the impact of the BRI scheme on Malaysia's geopolitics and economy. This research employs two analytical lenses: geopolitics and international cooperation. It examines the regional dynamics that have emerged due to Malaysia's partnership with the BRI and assesses the potential impact of BRI at the domestic level. Qualitative research methods were used, and data was collected through library research. The research indicates that Malaysia's geopolitics have shifted following the implementation of the BRI scheme, resulting in an economic upturn through the utilization of the newly constructed infrastructure. BRI has had a positive impact on Malaysia. Specifically, it has led to an increase in container traffic and contributed to the country's GDP. Additionally, the BRI has helped to develop Malaysia's Eastern region. The results of BRI have affected Malaysia's position in both geopolitical and economic aspects within ASEAN. In conclusion, the BRI has positively impacted Malaysia since its reinstatement in 2018.